Publications of Tuvan Fairy Tales and Heroic Tales in Russian during the Soviet Period: an aspect of Memory Policy - Krasilnikova, Ekaterina I.; Troyak, Irina S. (The New Research of Tuva, 2025)
The article characterizes the influence of Soviet memory policy on the publication of Tuvan fairy tales and heroic epics in Russian-language book editions of the 1950s–1980s. During the study, 19 editions (including reprints) of Tuvan fairy tales and heroic epics in Russian were identified, along with 23 collections of fairy tales from various peoples that contained works of Tuvan folklore. The authors identified the conditions and factors influencing the publication of Russian-language books containing Tuvan folk tales and revealed the political and ideological contexts of compiling these collections. These contexts are interpreted as part of the broader project of shaping Soviet culture—national in form, socialist in content. The study also highlights the universalist meanings embedded in Soviet memory policy, which influenced the preparation of fairy tales for publication. The article provides examples of content changes in specific fairy tales from one edition to another, driven by state memory policy. The study identifies key qualitatively distinct stages in the publication of fairy tale collections. It also demonstrates the differences between the living folklore tradition and fairy tales as part of book culture, as well as the superficiality of cultural changes in Soviet-era Tuva, as reflected in the practice of publishing folk tales.